Feeding Trial Evaluating Mazuri® Nestling Meal Compared to FoNS© as a Diet for Nestling and Fledgling Passerines in a Rehabilitation Setting - Seage, Eileen; Miller, Erica; Koutsos, Elizabeth (Wildlife Rehabilitation Bulletin, 2010)
Formula for Nestling Songbirds (FoNS©) is a diet commonly fed to nestling and fledging passerines in rehabilitation settings. The authors evaluated a new formulation, Mazuri® Nestling Meal (MNM), as a potential commercial alternative to FoNS©. The objective was to evaluate the adequacy of MNM compared to FoNS© in birds presented to Tri–State Bird Rescue & Research between 10 June and 10 August 2009. Clutchmates were randomly assigned to FoNS© (control group) or MNM (experimental group) and fed on the same schedule to satiety. Birds received species–appropriate dietary supplementation. Birds were discharged from the study when they moved outside, died, or were removed by a clinician due to health status. The primary endpoint was rate of weight gain, as determined by the percent of admission body weight gained per day. The mean of the control population (n=27) was compared with the experimental population (n=27) using the Student’s t–test, with statistical significance set at p<0.05. The mean percentage body weight gain per day for the control group was 4.57 (95% CI 2.825–6.310). The mean percentage body weight gain per day for the experimental group was 3.89 (95% CI 2.145–5.631). The difference between populations was not statistically significant as indicated by p=0.58. The control group had one death. The experimental group had three deaths and three birds removed by clinician (two subsequently euthanized). With the exception of one inconclusive result, necropsies performed by the overseeing clinician determined cause of death to be unrelated to diet. The statistical analysis and additional qualitative data suggests that MNM is equivalent to FoNS© and an acceptable alternative.